Biomechanics of ramp descent in unilateral trans-tibial amputees: Comparison of a microprocessor controlled foot with conventional ankle–foot mechanisms. (February 2016) - Struchkov, Vasily; Buckley, John G.
Abstract: Background : Walking down slopes and/or over uneven terrain is problematic for unilateral trans-tibial amputees. Accordingly, 'ankle' devices have been added to some dynamic-response feet. This study determined whether use of a microprocessor controlled passive-articulating hydraulic ankle–foot device improved the gait biomechanics of ramp descent in comparison to conventional ankle–foot mechanisms. Methods : Nine active unilateral trans-tibial amputees repeatedly walked down a 5° ramp, using a hydraulic ankle–foot with microprocessor active or inactive or using a comparable foot with rubber ball-joint (elastic) 'ankle' device. When inactive the hydraulic unit's resistances were those deemed to be optimum for level-ground walking, and when active, the plantar- and dorsi-flexion resistances switched to a ramp-descent mode. Residual limb kinematics, joints moments/powers and prosthetic foot power absorption/return were compared across ankle types using ANOVA. Findings : Foot-flat was attained fastest with the elastic foot and second fastest with the active hydraulic foot ( P < 0.001). Prosthetic shank single-support mean rotation velocity (p = 0.006), and the flexion ( P < 0.001) and negative work done at the residual knee ( P = 0.08) were reduced, and negative work done by the ankle–foot increased ( P < 0.001) when using the active hydraulic compared to the other two ankle types. Interpretation : The greater negative 'ankle' work done when using the active hydraulic compared to other two ankle types, explains why there was a corresponding reduction in flexion and negative work at the residual knee. These findings suggest that use of a microprocessor controlled hydraulic foot will reduce the biomechanical compensations used to walk down slopes. Highlights: Walking down/descending slopes is problematic for unilateral trans-tibial amputees. We compare ramp descent using microprocessor-controlled foot with conventional feet. Negative 'ankle' work during descent increased using microprocessor-controlled foot. Residual-knee flexion and negative work decreased with microprocessor-controlled foot. Use of a microprocessor-controlled foot should make descending slopes less problematic.